1999
DOI: 10.1074/jbc.274.40.28626
|View full text |Cite
|
Sign up to set email alerts
|

Selective Up-regulation of Fatty Acid Uptake by Adipocytes Characterizes Both Genetic and Diet-induced Obesity in Rodents

Abstract: Long chain fatty acid transport is selectively up-regulated in adipocytes of Zucker fatty rats, diverting fatty acids from sites of oxidation toward storage in adipose tissue. To determine whether this is a general feature of obesity, we studied [ 3 H]oleate uptake by adipocytes and hepatocytes from 1) homozygous male obese (ob), diabetic (db), fat (fat), and tubby (tub) mice and from 2) male Harlan Sprague-Dawley rats fed for 7 weeks a diet containing 55% of calories from fat. V max and K m were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 57 publications
3
64
1
Order By: Relevance
“…6,7,9 The former suggestion was supported by strong correlations between plasma insulin and the V max for adipocyte LCFA uptake in obese and nonobese humans. 8 While leptin is an insulin counter-regulatory hormone in some settings, 50 in others its effects parallel those of insulin.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…6,7,9 The former suggestion was supported by strong correlations between plasma insulin and the V max for adipocyte LCFA uptake in obese and nonobese humans. 8 While leptin is an insulin counter-regulatory hormone in some settings, 50 in others its effects parallel those of insulin.…”
Section: Discussionmentioning
confidence: 84%
“…22 Fatty acid uptake studies Long chain fatty acid uptake kinetics by adipocyte suspensions were measured by rapid filtration using tracer amounts of [ 3 H]-oleic acid (OA). 3,6 As previously, 3,[6][7][8][9]23 data for OA uptake were best fitted by the sum of a saturable plus a nonsaturable function of the unbound OA concentration in the incubation medium, of the form:…”
Section: Adipocyte Isolation and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 We have also shown that obesity resulting from a variety of causes (eg genetic, dietary) in several rodent species is associated with the tissue-specific upregulation of saturable LCFA uptake by adipocytes, but not by hepatocytes or cardiac myocytes. 3,4 These findings suggest (1) that the selective upregulation of adipocyte LCFA uptake in obesity alters LCFA partitioning, diverting LCFA away from tissues where they would be consumed as fuel to adipose tissue, where they are stored as triglycerides; and (2) that the increase in saturable LCFA uptake reflects upregulation of specific membrane transport process(es). In animal models such as the ob/ob mouse, insulin appears to be an important upregulator and leptin a key downregulator of adipocyte LCFA uptake.…”
Section: Introductionmentioning
confidence: 99%